Analisis Kinerja Lalu Lintas Jalan Pengayoman Pada Segmen Jl.Bougenville-Jl.Adyaksa - Sufiati Bestari; Mary Selintung; Lus Aini Marlina (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
On Pengayoman road, the traffic flow is dominated by working employees and shoppers along Pengayoman road in the Jl.Bougenville-Jl.Adyaksa segment. This causes traffic conditions to be congested at certain hours and can affect traffic performance. In addition, activities carried out beside the road are also an influence on traffic performance, namely the stopping of public vehicles due to passengers getting on and off, retailers in the road median, and the number of vehicles parking on the road. This study aims to determine the traffic performance of Jalan Pengayoman on the Jl.Bougenville-Jl.Adyaksa section, while the things that need to be studied are the degree of saturation, the average speed value of light vehicles, and the actual average speed value of light vehicle spaces during peak hours. The analysis in this study refers to PKJI 2014. Data collection was carried out for 3 days, namely enumerating traffic volumes, enumerating the incidence of side obstacles, and measuring travel time on light vehicles. The results of the analysis show that the degree of saturation in the west-east direction is 0.37 and the east-west direction is 0.51 which is less than 0.85, meaning that the traffic flow in both directions has not been jammed. Based on the reading of the graph, the average speed of light vehicles in the west-east direction is 56 km/h and in the east-west direction is 52.5 km/h. The calculation of the speed value and the reading on the graph have very different results because the survey distance is too short to get the space speed, which is 50 m. It is recommended that in conducting speed surveys the distance is too short to get the space speed. It is recommended that in conducting a speed survey the distance used for the average speed of space should be more than 50 m to get results that are more representative of the speed of space.